Evidence for the Absence of La Crosse Virus, Rift Valley Fever Virus, and Bunyamwera Virus in Korean Domestic Pigs - Hee-Chun Chung; Van-Giap Nguyen; Bong-Kyun Park (International Journal of Negative Results, 2017)
A surveillance study reports no detection of targeted bunyaviruses in domestic pigs in Korea. Methods, sampling frame, and assay limits are described to contextualize interpretation and surveillance value.
Keywords: LACV